Foreigners in the Russian petroleum sector: the cases of Sakhalin-II and TNK-BP - Goes, Sander Bernardus (Universitetet i Tromsø, 2013)
This thesis is an attempt to better understand the sometimes tumultuous relations between international oil companies (IOCs) and the Russian state by examining conflicts over regulatory practices and the enforcement of environmental regulations, and their interpretation in the Western media. This research focuses on two cases, one involving Royal Dutch Shell, the majority owner of company Sakhalin Energy, and the other involving BP’s Russian joint venture, TNK-BP. The two cases were selected as windows on the changing relationship between the state and IOCs in Russia during a specific political era – the first two presidencies of Vladimir Putin. This was also a period during which oil prices rose steadily and remained at historically high levels. Such periods tend to strengthen the hand of oil-producing states and strain their relations with IOCs. Sakhalin Energy is the operator of the Sakhalin II project, and was until December 2006 controlled by Shell and later by the Russian state company Gazprom. TNK-BP was the main owner of the Kovykta natural gas field which was central to the conflict – initially between the Russian authorities and a united TNK-BP and later on between the Western and Russian shareholders in TNK-BP. In the cases of both BP and Shell, the Russian authorities accused the IOCs of violating formal regulations, such as environmental regulations. The sanctions that the Russian authorities imposed on the IOCs and their motivations for doing so were the subject of extensive discussion among IOCs, other Western actors and the Western media. This dissertation aims to find out how Western actors such as the media and IOCs understand the rules of the game in Russia, relating it to Alena Ledeneva’s work. Ledeneva (2006) outlines a framework explaining the enforcement of regulations and regulatory practices in Russia and their use and abuse for informal purposes. Her main point is that law enforcement practices in Russia differ from those in the West because in Russia regulations are often used ...